Leptin in the Respiratory Tract: Is There a Role in SARS-CoV-2 Infection? - Bruno, Andreina; Ferrante, Giuliana; Di Vincenzo, Serena; Pace, Elisabetta; La Grutta, Stefania (Frontiers in Physiology, 2021)
Leptin is a pleiotropic adipocytokine involved in several physiologic functions, with a known role in innate and adaptive immunity as well as in tissue homeostasis. Long and short isoforms of leptin receptors are widely expressed in many peripheral tissues and organs, including the respiratory tract. Likewise leptin, microbiota affects the immune system and may interfere with lung health through bidirectional crosstalk called the "gut-lung axis". Obesity leads to impaired protective immunity and altered susceptibility to pulmonary infections, as those by SARS-CoV2. Although it is known that leptin and microbiota link metabolism and lung health, actually their role within the SARS-CoV2 coronavirus disease 2019 (COVID-19) deserves further investigations. This review aims to summarize the available evidence about: (i) the role of leptin in immune modulation; (ii) the role of gut microbiota within the gut-lung axis in modulating leptin sensitivity; (iii) the role of leptin in the pathophysiology of COVID-19.